Analysis of the Effectiveness of Pop-Up Book Media on Science Learning in Elementary Schools - Maharani Zaniyati; Rohmani Rohmani (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2024)
Objective: Science education in elementary schools provides basic scientific knowledge and skills and develops students' critical and creative thinking abilities. This study aims to analyze the effectiveness of using pop-up books as media in learning science in elementary schools. Method: In this study, researchers applied the Systematic Literature Review (SLR) method using the Google Scholar database. The literature search focused on the initial keyword